Komparasi Daya Matematis antara Siswa yang Diajar Melalui Strategi Pembelajaran TTW Dengan TAPPS - Titi Pujiarti (AL-FURQAN, 2017)
The research aimed to discover the description, the difference of the improvement of Mathematical Powers of students who were taught by using cooperative learning TTW strategy TAPPS strategy to class VIII students at SMPN 26 Makassar. This research is a quasi-experimental research, using the h pretest-posttest two group design. The population in this study in a class VIII at SMPN 26 Makassar on the academic year 2016/2017 by number of 250 students. The study involved two experimental class, the class VIII 3 consisting of 28 student and class VIII 4 which consists of 28 student selected by simple random sampling. The first experimental class was treated by applying cooperative learning with TTW strategy and and the second experimental class was treated by applying TAPPS strategy. The instruments of the research were Mathematical power test, learning implementation observation sheet, and students’ activities observation sheet. The data obtained were analyzed using descriptive statistics and inferential statistical analysis using analysis of Multivariate Analysis of Varian (MANOVA). The results of the research showed that (1) Mathematical powers (concept understanding ability) after the implementation of cooperative learning with TTW strategy were in high category, Mathematics communication abilities were in medium category, Mathematics problem solving abilities were in high category and the improvement of Mathematical powers in high category. And Mathematical powers (concept understanding ability, Mathematics communication, and Mathematical problem solving) after the implementation of cooperative learning with TAPPS strategy were in medium category, Mathematical powers in medium category, (2) there was difference of improvement of Mathematical powers of students who were taught by using TTW strategy and TAPPS strategy. (3) there was no difference of the improvement of Mathematics concept understanding abilities who were taught by using TTW strategy and TAPPS strategy (4) there was a difference of the improvement of Mathematics communication abilities of the students who were taught by using TAPPS strategy, and (5) there was a difference of the by using TTW strategy and TAPPS strategy to class VIII students at SMPN 26 Makassar